Implementasi Metode Technique For Order Preference By Similarity To Ideal Solution (Topsis) Dalam Penunjang Keputusan Penilaian Kinerja Guru - Ambar Tri Hapsari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The purpose of this research is to build a decision support system for evaluating teacher performance using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method at SDN Inpres 09 Bandung. decision support for teacher performance evaluation uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method which can be used by school principals and assessment teams to provide teacher performance assessments. If previously when not using the system in the teacher performance appraisal process it took 1 week, now with the teacher performance appraisal system, the selection time is shorter, namely 15 minutes to 30 minutes. So that routine activities within the scope of SDN Inpres 09 Bandung are not disturbed by the process of evaluating teacher performance, then the process of making reports becomes easier and more systematic.